INTERPRETASI MAKNA PAJAK ATAS RUMAH KOS DALAM PEMUNGUTAN PAJAK DAERAH : KAJIAN HERMENEUTIKA - Khoirul Hidayah (Arena Hukum, 2017)
AbstractCharging hotel tax for boarding house in Indonesian law The number 28, year 2009 about Regional Taxation and Retribution has social problem and has never fulfilled justice principal. Social fact shows that the function of boarding house is not merely for sleeping but also for living (primary need). One of purposes of formulating the law about charging hotel tax for boarding house is extending the object of regional taxation for increasing regional development through the rise of regional income. To fulfill the purpose of law constitution and also justice principal, the concept of charging hotel tax for boarding house must be distinguished. For making the new concept of charging hotel tax for boarding house, the first thing to do is to find the literal meaning of hotel and boarding house by applying hermeneutics theory. The research method is normatif with regulation and conceptual approach. The analysis result shows the new concept of hotel and boarding house taxation. The term ‘boarding house’ must be excluded from hotel concept and be another tax object. Fulfilling justice principal, the concept of charging hotel tax for boarding house written in the article 1, the law number 28, year 2009 must be reformed. AbstraksiPemungutan pajak hotel atas rumah kos dalam UU No. 28 Tahun 2009 tentang Pajak Daerah dan Retribusi Daerah (UU PDRD) memiliki persoalan sosial dan juga belum memenuhi prinsip keadilan. Fakta sosial menunjukkan bahwa fungsi rumah kos adalah bukan sekedar sebagai tempat menginap, namun juga sebagai tempat tinggal (kebutuhan primer). Guna memenuhi tujuan peraturan perundang-undangan dan juga memenuhi prinsip keadilan, maka konsep pemungutan pajak hotel atas rumah kos semestinya harus dibedakan. Tujuan penelitian adalah untuk membuat konsep baru pajak hotel yang terdapat di dalam UU PDRD. Jenis penelitian adalah normatif dengan pendekatan peraturan perundang-undangan dan pendekatan konsep. Guna membuat konsep baru pemungutan pajak atas rumah kos, maka terlebih dahulu mencari makna sebenarnya hotel dan rumah kos melalui metode hermeneutika Gadamer. Berdasarkan hasil analisis, maka diperoleh konsep baru pajak hotel dan pajak rumah kos. Istilah rumah kos harus dikeluarkan dari konsep hotel, dan menjadi obyek pajak tersendiri. Guna memenuhi prinsip keadilan, maka konsep pemungutan pajak hotel atas rumah kos UU No.28 Tahun 2009 harus diubah.